Reactions of Palm Oil-Based mcl-PHAs with Epoxidized Natural Rubber - Lee, S.Y.; Hassan, A.; Tan, I.K.P.; Terakawa, K.; Ichikawa, N.; Gan, S.N. (Wiley, 2010)
A palm oil-based medium-chain-length polyhydroxyalkanoate (mcl-PHA) was allowed to react with epoxidized natural rubber (ENR). There was no noticeable reaction at ambient temperature for short reaction times. However, after 30 min at 170 degrees C, the mcl-PHA underwent thermal degradation to generate carboxylic terminal groups that attacked the epoxy groups of the ENR. Evidence of the ring-opening reaction was provided by both FTIR and (1)H-NMR. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 115: 2039-2043, 2010